Recherches sur les édifices ibadites du Djebel Nafūsa - Prevost, Virginie (Acta Orientalia Belgica, 2014)
The Nafūsa Mountains, known as a stronghold of Berber Ibadism, have developed an extremely rich vernacular architecture. Little rural mosques abound in the jabal, which may occasionally go back to the eight or ninth centuries AD. Some mosques are associated with scholars or chiefs quoted in mediaeval Ibadi texts, or with the Christian past of the region. Many are semi-subterranean and present in the prayer hall noteworthy decorations carved out of the plastering. The three remaining communal fortified granaries also are of particular interest. All those Ibadi buildings will be studied in a forthcoming publication.
Keywords: Architecture – Djebel Nefousa

Les mosquées ibadites du djebel Nafūsa: Architecture, histoire et religions du nort-ouest de la Libye (VIIe-XIIIe siècle). - Prevost, Virginie; Derriks, Axel; Favresse, Mathieu (Society for Libyan Studies, 2016)
Keywords: Architecture – Djebel Nefousa

Quelques mosquées anciennes du djebel Nafūsa et leur évocation dans les sources ibadites - Prevost, Virginie (Actes de la 1re journée d'études sur la Libye antique et médiévale (30 janvier 2010, Sorbonne, Paris), 2012)
Keywords: Architecture – Djebel Nefousa